Analyzing 7th Graders' Simple Present Errors in Descriptive Writing: Analisis Kesalahan Dominan Penggunaan Tenses Present Sederhana dalam Teks Deskriptif pada Siswa Kelas Tujuh - Azza Hikmiawati; Vidya Mandarani (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate the dominant errors in the use of the simple present tense by seventh grade students when writing descriptive texts. The qualitative research method was employed, utilizing data analysis techniques to process the collected information. The population consisted of 45 students from two different classes at SMP Muhammadiyah 10, with 37 students' exercise results being analyzed. The data was obtained from students' written compositions in which they employed the simple present tense to describe various subjects. The findings revealed four major error types: omission (46.90%), addition (16.04%), misformation (27.16%), and misordering (9.90%). Among these, omission errors were the most prevalent, comprising 38 errors or 46.90% of the total. The results emphasize the need for targeted instruction and practice to enhance students' mastery of the simple present tense in writing descriptive texts, thereby improving their overall English language proficiency. Highlights: Error analysis: Identifying and analyzing errors in the use of simple present tense in descriptive texts. Seventh grade students: Evaluating the proficiency of students in using the simple present tense. Qualitative method: Employing a qualitative approach to gather and analyze data on error patterns in descriptive writing. Keywords: simple present tense, descriptive texts, error analysis, seventh grade students, qualitative method.